THE EFFECT OF Beauveria bassiana APPLICATION TO CONTROL MAIN PESTS OF STRING BEANS (Vigna sinensis) ON PLANT DAMAGE AND YIELD - Hanafi Nursahid; Rukmowati Brotodjojo; Oktavia Sarhesti Padmini (UNIVERSITAS PEMBANGUNAN NASIONAL ”VETERAN” YOGYAKARTA, 2019)
String beans productivity decreases every year. One of the causes is pest attacks. Pest control using Beauveria bassiana is an enviromentally friendly pest control. The aim of this study was to determine of the effect B. bassiana’s application to control string beans main pests, determine the best B. bassiana application frequency to control pest attacks and determine the correlation between main pests population and plant damage and yield of string beans. This study was conducted in Krebet, Sendangsari, Pajangan, Bantul, Daerah Istimewa Yogyakarta in Januari – April 2019. This study used a single factor experiment arranged in a Randomized Completely Block Design (RCBD). This study used the following treatments: once application of B. bassiana at 5 weeks after planting (wap), two times application of B. bassiana at 3 wap (week after planting) and 7 wap, three times application of B. bassiana at 3 wap, 5 wap and 7 wap, four times application of B. bassiana at 3 wap, 4 wap, 6 wap and 7 wap, five times application of B. bassiana at 3 wap, 4 wap, 5 wap, 6 wap and 7 wap, negative control (without B. bassiana application) and positive control (synthetic insectiside profenofos application). The results of the study showed that B. bassiana could control Aphis craccivora. The best B. bassiana application frequency was 5 times at 3 wap, 4 wap, 5 wap, 6 wap and 7 wap. Leaves damage increased as the population of leaf beetles increased. Yield of string beans decreased as the population of A. craccivora and leaf beetles increased as well as the leaves damage increased.Keyword: main pests, Beauveria bassiana, damage, string beans, yield